2016
DOI: 10.1080/14733285.2016.1190812
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing nature and children’s conceptualizations of the natural world

Abstract: This paper examines young children's concept of nature, paying attention to the role played by types of daily experience with nature on 832 children's constructions of the natural world. We observed the roles of three types of experiences, as determined by the children's place of residence (urban, rural mountain range and rural agricultural).Participants wrote what they thought about when hearing the word 'nature'. Content analysis revealed an overarching two-level conceptual structure formed with four underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 26 publications
(40 reference statements)
5
37
0
6
Order By: Relevance
“…Many children in our study expressed strong positive feelings about spending time in the forest garden, and some of them also talked in more general terms about their appreciation of spending time in 'nature'. Research shows that students' perceptions of the term 'nature' depend on socioeconomic factors, gender, previous experiences of nature, age/cognitive development and influences from media (Collado, Íñiguez-Rueda, & Corraliza, 2016;Rickinson, 2001). Children mostly see themselves as separate from the natural world (Payne, 1998;Phenice & Griffore, 2003), but at the same time, they often have a clear sense of the connection between themselves, natural processes and other aspects of the natural world (Bonnett & Williams, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Many children in our study expressed strong positive feelings about spending time in the forest garden, and some of them also talked in more general terms about their appreciation of spending time in 'nature'. Research shows that students' perceptions of the term 'nature' depend on socioeconomic factors, gender, previous experiences of nature, age/cognitive development and influences from media (Collado, Íñiguez-Rueda, & Corraliza, 2016;Rickinson, 2001). Children mostly see themselves as separate from the natural world (Payne, 1998;Phenice & Griffore, 2003), but at the same time, they often have a clear sense of the connection between themselves, natural processes and other aspects of the natural world (Bonnett & Williams, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The possible positive impact of direct and visual contact with non-human animals on people’s pro-environmentalism also needs further consideration [see Young et al (2018) for a review]. Finally, the word nature can have different meanings for people from different cultures (Wohlwill, 1983; Collado et al, 2016; Profice, 2018) and as such the definition of experiences in nature should take into account participants’ cultural background. For instance, some people may consider humans are part of nature while others may not (Wohlwill, 1983; Mayer and Frantz, 2004) and differences in the esthetic perception of nature have consequences for biodiversity protection (Williams and Cary, 2002).…”
Section: Future Researchmentioning
confidence: 99%
“…daily life) for 8-to 16-year-old children (see also Elliot et al, 2014). Collado, Íñiguez-Rueda and Corraliza (2016) studied the effects of children's daily experiences of nature on their conceptualization of the natural world. They found that children from rural settings, who had more direct experience with nature, were more likely to engage in conversations about nature than children from urban environments (see also Genovart, Tavecchia, Enseñat, & Laiolo, 2013).…”
Section: 'mentioning
confidence: 99%